Structural design considerations for super-tall buttressed core structure: the Burj Khalifa - Peirce, Kai (Kansas State University, 2023)
The intent of this report is to illustrate the design and feasibility considerations for super-tall buttressed core structures in respect to the Burj Khalifa. Utilizing the latest construction surveying equipment and engineering practices has led to taller structures and more sophisticated methods of analysis. With realization of such heights, the Burj Khalifa poses as a benchmark for structural analysis methods and future structures. Dynamic considerations for structures vary from many factors such as overall stiffness, damping, and mass. For better understanding of global behaviors, early integration of aerodynamic shaping and wind engineering played a major role in mitigating and taming the dynamic wind effects. Understanding the structural and foundation system behaviors of the tower were the key fundamental drivers for the development and execution of a state-of-the-art survey and structural health monitoring programs. These programs will be further described as well as their ability to measure accelerations, deflections, strains, concrete shortening, and settlements of structural members. Furthermore, this report describes the foundation design process adopted for the Burj Khalifa. The foundation system is a compensated piled raft, founded on very heterogenous soil deposits. Geotechnical investigations, field and laboratory testing programs, and the design process will all discuss how various design issues were addressed. The various design issues addressed include: ultimate capacity, overall stability under wind and seismic loadings, and settlement and differential settlements.
Keywords: Burj Khalifa; Reinforced concrete; Wind engineering; Raft foundation